2007
DOI: 10.1074/jbc.m609076200
|View full text |Cite
|
Sign up to set email alerts
|

The p38α/β Mitogen-activated Protein Kinases Mediate Recruitment of CREB-binding Protein to Preserve Fast Myosin Heavy Chain IId/x Gene Activity in Myotubes

Abstract: In skeletal muscle, the transformation of fast into slow fiber type is accompanied by shifts in fiber type-specific gene expression that includes down-regulation of the adult fast fiber myosin heavy chain IId/x (MyHCIId/x) gene. Here, we report that the mitogen-activated protein kinases (MAPKs) p38␣/␤ regulate MyHCIId/x gene expression. Electrical stimulation of rabbit skeletal muscle cells with a slow fiber type activity pattern and treatment of C2C12 myotubes with Ca 2؉ -ionophore inhibited p38␣/␤ MAPKs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 58 publications
(41 reference statements)
2
14
0
Order By: Relevance
“…Murgia et al (31) suggested that the Ras-ERK pathway was required for reestablishment of the slow fiber program in a model simulating nerve impulse activity. p38 MAPK has been reported to control MyHC IIx promoter activity in myotubes (27). Our study demonstrated that CMHS did not enhance the activity of either ERK1/2 or p38 MAPK.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…Murgia et al (31) suggested that the Ras-ERK pathway was required for reestablishment of the slow fiber program in a model simulating nerve impulse activity. p38 MAPK has been reported to control MyHC IIx promoter activity in myotubes (27). Our study demonstrated that CMHS did not enhance the activity of either ERK1/2 or p38 MAPK.…”
Section: Discussionsupporting
confidence: 40%
“…Several studies have shown that MAPKs are involved in the determination of muscle fiber type phenotypes (27,31). It is possible that heat stress affected the phosphorylation of ERK1/2 or p38 MAPK.…”
Section: C145 Mild Heat Stress Induces a Shift Of Muscle Fiber Typementioning
confidence: 99%
See 1 more Smart Citation
“…We used DNP-specific immunoreactivity on carbonyl groups as a marker of protein oxidation in protein bands at four different molecular weights (25,28,43, and 67 kDa). We found no difference between the AL and CR groups for this Values are means Ϯ SE; n ϭ 8 -12 muscles per diet group.…”
Section: Protein Oxidationmentioning
confidence: 99%
“…Multiple members of a family of serine-threonine kinases called mitogen-activated protein kinases (MAPKs) can function as negative regulators of insulin sensitivity. Skeletal muscle highly expresses the JNK1 and JNK2 isoforms of c-Jun NH 2 -terminal kinase (6,14), the ERK1 and ERK2 isoforms of extracellular signal-regulated kinase (62), and the p38␣, p38␤, and p38␥ isoforms of p38 MAPK (43,53). Excessive JNK activation has been frequently implicated in the development of insulin resistance (32,34).…”
mentioning
confidence: 99%